Population screening for glucose-6-phosphate dehydrogenase deficiency using quantitative point-of-care tests: a systematic review - Zailani, Mohamed Afiq Hidayat; Raja Sabudin, Raja Zahratul Azma; Ithnin, Azlin; Alauddin, Hafiza; Sulaiman, Siti Aishah; Ismail, Endom; Othman, Ainoon (Frontiers in Genetics, 2023)
Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an X-linked hereditary disorder and a global public health concern that is most prevalent in malaria-endemic regions including Asia, Africa, and the Mediterranean. G6PD-deficient individuals are at high risk of developing acute hemolytic anemia following treatment with antimalarial drugs including Primaquine and Tafenoquine. However, the currently available tests for G6PD screening are complex and often have been misclassifying cases, particularly for females with intermediate G6PD activity. The latest innovation of quantitative point-of-care (POC) tests for G6PD deficiency provides an opportunity to improve population screening and prevent hemolytic disorders when treating malaria. Aim(s): To assess the evidence on the type and performance of quantitative point-of-care (POC) tests for effective G6PD screening and hence, radical elimination of Plasmodium malaria infections. Methods: Relevant studies published in English language confined from two databases, Scopus and ScienceDirect were searched from November 2016 onwards. The search was conducted using keywords including “glucosephosphate dehydrogenase” or “G6PD”, “point-of-care”, “screening” or “prevalence”, “biosensor” and “quantitative”. The review was reported following the PRISMA guidelines. Results: Initial search results yielded 120 publications. After thorough screening and examination, a total of 7 studies met the inclusion criteria, and data were extracted in this review. Two types of quantitative POC tests were evaluated, namely, the CareStartTM Biosensor kit and the STANDARD G6PD kit. Both tests showed promising performance with high sensitivity and specificity ranging mostly from 72% to 100% and 92%–100%, respectively. The positive and negative predictive values (PPV and NPV) ranged from 35% to 72% and 89%–100%, with accuracy ranging from 86% to 98%. Conclusion: In areas with a high prevalence of G6PD deficiency that overlap with malaria endemicity, availability and validation of the diagnostic performance of quantitative POC tests are of absolute importance. Carestart™ biosensor and STANDARD G6PD kits showed high reliability and performed well in comparison to the spectrophotometric reference standard.